Study on strain relaxation in AlGaN/GaN superlattices grown by metal-organic chemical vapor deposition. (October 2021) - Yang, Shixu; Wang, Yang; Deng, Gaoqiang; Yu, Ye; Niu, Yunfei; Zhang, Lidong; Yu, Jiaqi; Lu, Chao; Zhang, Yuantao
Abstract: In this work, AlGaN/GaN superlattices (SLs) structures were grown on SiC substrates by metal-organic chemical vapor deposition (MOCVD). The influence of AlGaN/GaN period numbers, the ratio of AlGaN thickness to GaN thickness ( t A l G a N / t G a N ), and the Al content on the strain state of AlGaN/GaN SLs are investigated. Moreover, the strain relaxation mechanism of the SLs is analysed. Our results show that the surface roughening, the formation of misfit dislocations and the generation of cracks are all contribute to the strain relaxation of the SLs. Moreover, the main reason cause the formation of cracks in the SLs is the large lattice mismatch between the SLs and the template rather than the large lattice mismatch between the GaN and AlGaN in the SLs. It is worth noting that understanding the strain relaxation mechanism is crucial for the design and fabrication of high-quality optoelectronic devices based on AlGaN/GaN SLs by MOCVD. Highlights: The strain states of MOCVD-grown AlGaN/GaN superlattices (SLs) are studied. The strain relaxation mechanism of AlGaN/GaN SLs is analysed. Large lattice mismatch between SLs and template causes the formation of cracks.